Technical and practical innovations to reduce soil and water losses by improving soil physical properties - Bahddou, Sophia (Cranfield University, 2024)
Soil erosion is a significant environmental challenge that impacts agricultural productivity, environmental sustainability, and food security. The aim of this research is to better understand the processes of soil erosion by water and wind under different tillage and agronomic measures, with a view to reduce soil and water losses. The research is divided into three main studies. The first study examines the effects of soil surface roughness (SSR) orientation and magnitude on runoff, infiltration, and soil erosion under simulated rainfall conditions. Treatments included up- and downslope, across-slope, random SSR, and a smooth surface. The second study explores the combined effects of wind and rainfall on soil erosion using a novel system comprising rainfall and wind simulators. The study evaluates the role of wind-driven rain (WDR) with varying wind velocities on surface runoff, infiltration, and soil loss, comparing smooth and rough soil surfaces. The third study assesses the influence of different wheat lines (wild type vs dwarf), water regimes (dry vs well-watered), and sowing densities on plant traits, soil properties and predicted erosion rates. The outcome of this research indicates that i) random SSR significantly increases runoff and soil loss, while across-slope SSR does not consistently reduce erosion compared to up- and downslope oriented SSR, ii) WDR significantly accelerates runoff generation and increases soil loss compared to windless rain, with higher wind velocities magnifying these effects, iii) initial SSR patterns change during rainfall events, and WDR exacerbates these changes in SSR, iv) dwarf wheat, higher sowing density and well-watered conditions significantly reduce erosion rates through improved aboveground and belowground plant traits and soil properties, particularly at the later stage of plant growth. In conclusion, this research highlights the importance of considering SSR, wind effects, and plant traits in soil erosion studies to develop effective soil conservation strategies and enhance agricultural sustainability.
Rickson, R. Jane - Associate Supervisor
Keywords: Drought; Infiltration; Raindrop impact; Rainfall erosivity; Rainfall simulator; Roots; Runoff; Shoots; Soil erosion; Soil surface roughness; Splash erosion; Wind-driven rain; Wheat; Wind tunnel